2015
DOI: 10.1002/stem.2042
|View full text |Cite
|
Sign up to set email alerts
|

Neural Stem Cells in the Adult Subventricular Zone Oxidize Fatty Acids to Produce Energy and Support Neurogenic Activity

Abstract: Neural activity is tightly coupled to energy consumption, particularly sugars such as glucose. However, we find that, unlike mature neurons and astrocytes, neural stem/progenitor cells (NSPCs) do not require glucose to sustain aerobic respiration. NSPCs within the adult subventricular zone (SVZ) express enzymes required for fatty acid oxidation and show sustained increases in oxygen consumption upon treatment with a polyunsaturated fatty acid. NSPCs also demonstrate sustained decreases in oxygen consumption up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(108 citation statements)
references
References 39 publications
7
98
1
2
Order By: Relevance
“…This observation, which confirms previous findings on the key role of FA oxidation (FAO) in HSC self-renewal [36], is particularly relevant, since inborn defects in FAO are associated with developmental neuropsychiatric disorders including autism in humans [37]. Of note, FAO capacity is not restricted to embryonic NSCs, but also occurs in adult cells from SVZ [38].…”
Section: An Emerging Determinant In Nsc Fate Decisions: Lipid Metabolismsupporting
confidence: 90%
See 2 more Smart Citations
“…This observation, which confirms previous findings on the key role of FA oxidation (FAO) in HSC self-renewal [36], is particularly relevant, since inborn defects in FAO are associated with developmental neuropsychiatric disorders including autism in humans [37]. Of note, FAO capacity is not restricted to embryonic NSCs, but also occurs in adult cells from SVZ [38].…”
Section: An Emerging Determinant In Nsc Fate Decisions: Lipid Metabolismsupporting
confidence: 90%
“…These studies have indeed confirmed that NSC exit from quiescence is marked by downregulation of glycolysis [37], and FAO [38], and by an increase in ribosome biogenesis, protein synthesis, and mitochondrial oxidative phosphorylation.…”
Section: An Emerging Determinant In Nsc Fate Decisions: Lipid Metabolismmentioning
confidence: 54%
See 1 more Smart Citation
“…Under normal conditions, SVZ neural precursors depend on fatty acid oxidation for proliferation (Stoll et al, 2015), while baseline and exercise-induced hippocampal neurogenesis and cognitive enhancement require brain fatty acid synthesis (Chorna et al, 2013;Knobloch et al, 2013). However, alterations in lipid metabolism are associated with many cognitive disorders, including Huntington's, Parkinson's, and Niemann-Pick's diseases, as well as AD (Adibhatla and Hatcher, 2008;de la Monte and Tong, 2014;Guschina et al, 2011;Martinez-Vicente et al, 2010;Merlo et al, 2010;Sharon et al, 2003).…”
Section: Niche Lipid Metabolism: a Regulator Of Nscsmentioning
confidence: 99%
“…In the forebrain subventricular zone (SVZ) niche, lipid metabolism genes are among the major classes of transcriptional differences between quiescent and activated NSCs (Codega et al, 2014). Moreover, in both SVZ and hippocampal dentate gyrus (DG) niches, neural precursors require fatty acid oxidation for proliferation (Chorna et al, 2013;Knobloch et al, 2013;Matsumata et al, 2012;Stoll et al, 2015). NSCs are positioned particularly well in the SVZ to be regulated by environmental lipid signals.…”
Section: Introductionmentioning
confidence: 99%